PRINCIPAL LEARNING LEADERSHIP: INTEGRATING SPIRITUAL AND MORAL VALUES IN EDUCATIONAL SETTINGS - Effendi, Yulius Rustan (International Journal of Education, 2025)
This research aims to describe the role of school principals' learning leadership to empower and develop teacher-teaching competencies in increasing students' achievement motivation based on spiritual-moral values. This study used a qualitative approach with a case study design. The research subjects were three principals and three senior teachers from three Catholic Middle School, Christian Middle School, and Muhammadiyah Islamic Middle School in Malang City, East Java, Indonesia. Techniques used to collect data through in-depth interviews, observation, and documentation studies. Data analysis used a modified descriptive analysis technique. Validate data by measuring the degree of transferability, confirmability, dependability, and credibility. The research findings show that principals' learning leadership based on moral values of spirituality restores teacher learning and increases student achievement motivation. The study results show that the leadership role of school principals has a practical impact on leveraging teacher learning competencies to influence students' achievement motivation. In conclusion, the leadership role of school principals based on spiritual-moral values has an impact on improving teacher teaching competence so that learning activities are of higher quality and increase student learning motivation. This research recommendation is a reference for school principals in Indonesia to implement an influential learning leadership role based on spiritual-moral values to remedy the low quality of learning.